Neurocognitive Function, Psychosocial Outcome, and Health-Related Quality of Life of the First-Generation Metastatic Melanoma Survivors Treated with Ipilimumab. (21st July 2020) - Rogiers, Anne; Leys, Christophe; Lauwyck, Justine; Schembri, Adrian; Awada, Gil; Schwarze, Julia Katharina; De Cremer, Jennifer; Theuns, Peter; Maruff, Paul; De Ridder, Mark; Bernheim, Jan L.; Neyns, Bart
Abstract : Purpose . To assess neurocognitive function (NCF), psychosocial outcome, health-related quality of life (HRQoL), and long-term effects of immune-related adverse events (irAE) on metastatic melanoma survivors treated with ipilimumab (IPI). Methods . Melanoma survivors were identified within two study populations (N = 104 ), at a single-center university hospital, and defined as patients who were disease-free for at least 2 years after initiating IPI. Data were collected using 4 patient-reported outcome measures, computerized NCF testing, and a semistructured interview at the start and 1-year follow-up. Results . Out of 18 eligible survivors, 17 were recruited (5F/12M); median age is 57 years (range 33-86); and median time since initiating IPI was 5.6 years (range 2.1-9.3). The clinical interview revealed that survivors suffered from cancer-related emotional distress such as fear of recurrence (N = 8 ), existential problems (N = 2 ), survivor guilt (N = 2 ), and posttraumatic stress disorder (N = 6 ). The mean EORTC QLQ-C30 Global Score was not significantly different from the European mean of the healthy population. Nine survivors reported anxiety and/or depression (Hospitalization Depression Scale) during the survey. Seven survivors (41%) reported fatigue (Fatigue Severity Scale). Seven patients (41%) had impairment in NCF; only three out of seven survivors had impairment in subjective cognition (Cognitive Failure Questionnaire). Anxiety, depression, fatigue, and neurocognitive symptoms remained stable at the 1-year follow-up. All cases of skin toxicity (N = 8 ), hepatitis (N = 1 ), colitis (N = 3 ), and sarcoidosis (N = 1 ) resolved without impact on HRQoL. Three survivors experienced hypophysitis; all suffered from persistent fatigue and cognitive complaints 5 years after onset. One survivor who experienced a Guillain-Barré-like syndrome suffered from persisting depression, fatigue, and impairment in NCF. Conclusion . A majority of melanoma survivors treated with IPI continue to suffer from emotional distress and impairment in NCF. Timely detection in order to offer tailored care is imperative, with special attention for survivors with a history of neuroendocrine or neurological irAE. The trial is registered with B.U.N. 143201421920.